Improvement in corrosion resistance of 316L stainless steel in simulated body fluid mixed with antiplatelet drugs by coating with Ti-doped DLC films for application in biomaterials. (November 2022) - Wongpanya, Pornwasa; Wongpinij, Thipusa; Photongkam, Pat; Siritapetawee, Jaruwan
Abstract: The structures of pure (DLC), 5.33 at% Ti-doped (DLC:Ti_1), and 15.24 at% Ti-doped (DLC:Ti_2) DLC films coated on 316L SS were investigated using X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure spectroscopy. Their corrosion behavior was studied using electrochemical techniques. DLC:Ti_1 exhibited outstanding corrosion resistance with the lowest i corr and highest R p . Its corrosion resistance improved further when antiplatelet drugs [ticlopidine (T1) and aspirin (A1)] were present in the simulated body fluid (SBF), as indicated by the increase in the inhibition efficiency of DLC:Ti_1-SBF from 84.21 to 93.26 and to 97.04% for both DLC:Ti_1-A1 and DLC:Ti_1-T1, respectively. Graphical Abstract: ga1 Highlights: Pure and Ti-doped DLC films decreased the 316L SS corrosion rate in SBF. Antiplatelet drugs enhanced the corrosion resistance of DLC films. High TiO2 and low TiC contents of the DLC films improved corrosion resistance.